2007
DOI: 10.1017/s0003598x00095326
|View full text |Cite
|
Sign up to set email alerts
|

Early fig domestication, or gathering of wild parthenocarpic figs?

Abstract: Kislev et al.'s (2006a) recent claims of fig cultivation and domestication dated to the second half of the twelfth millennium BP in the Lower Jordan valley are sensational. For some, these finds are extremely significant and represent 'the oldest evidence for deliberate planting of a food-producing plant, as opposed to just gathering food in the wild' (Peter Bellwood in Gibbons 2006). There are, however, good reasons why these claims should not be taken at face value. Kislev et al. (2006a) present evidence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…These datasets testify to the significant contribution of tree crops to the south Levantine PPNA–EPPNB subsistence economies. While making a case for the ‘domestication’ of Pistacia and Ficus in the PPNA is doubtful (see especially the arguments for and against fig domestication by Kislev et al (2006) and Denham (2007), respectively), the integrated anthracological and seed botanical evidence suggests that Pistacia nuts were not simply collected from the wild as part of opportunistic strategies procuring occasional delicacies or dietary supplements. Instead, both Pistacia nut and fuel/timber wood production appear to have formed an integral part of the south Levantine PPN subsistence economies.…”
Section: Discussionmentioning
confidence: 99%
“…These datasets testify to the significant contribution of tree crops to the south Levantine PPNA–EPPNB subsistence economies. While making a case for the ‘domestication’ of Pistacia and Ficus in the PPNA is doubtful (see especially the arguments for and against fig domestication by Kislev et al (2006) and Denham (2007), respectively), the integrated anthracological and seed botanical evidence suggests that Pistacia nuts were not simply collected from the wild as part of opportunistic strategies procuring occasional delicacies or dietary supplements. Instead, both Pistacia nut and fuel/timber wood production appear to have formed an integral part of the south Levantine PPN subsistence economies.…”
Section: Discussionmentioning
confidence: 99%
“…11,200 cal BP) has been interpreted as a clear indication of human selection for this mutant infertile fig variety that remains on the tree longer and develops sweeter, softer fruit. Other researchers have noted, however, that parthenocarpy is known among wild female fig trees (Denham 2007; and therefore, as with the presence of tough-rachis varieties or larger cereal grains in low quantities, their occurrence in an archaeobotanical assemblage cannot be considered definitive proof of domestication. Kislev, Hartmann, and Bar-Yosef (2006b) have responded that if, as their critics contend, these figs represent the selective harvest of mutant figs from wild fig trees, at least some seeded varieties would be expected to have been collected along with these rare, naturally occurring parthenocarpic figs.…”
Section: New Archaeological Insights Into Plant Domesticationmentioning
confidence: 99%
“…Instead, this shrubby pioneer plant can be easily grown simply by replanting cut branches, a type of vegetative cloning that Kislev et al (2006a, b) contend is a form of domestication. Lev-Yadun et al (2006a) have subsequently argued, however, that since parthenocarpy is also found in wild female fig trees, which produce both seeded and unseeded figs, the seedless figs found at Gigal may well represent selective harvesting of these sweeter fruits from wild trees (see also Denham 2007). Kislev et al (2006b) discount this possibility, pointing out that all nine carbonized figs from Gigal and 313 single drupelets (small parts of aggregate fruit) represent parthenocarpic figs.…”
Section: Domestication Of Plantsmentioning
confidence: 99%